BNSTAVGABA-PVNCRF Circuit Regulates Visceral Hypersensitivity Induced by Maternal Separation in Vgat-Cre Mice - Huang, Si-Ting; Song, Zhi-Jing; Liu, Yu; Luo, Wen-Chen; Yin, Qian; Zhang, Yong-Mei (Frontiers in Pharmacology, 2021)
Visceral hypersensitivity as a common clinical manifestation of irritable bowel syndrome (IBS) may contribute to the development of chronic visceral pain. Our prior studies authenticated that the activation of the corticotropin-releasing factor (CRF) neurons in paraventricular nucleus (PVN) contributed to visceral hypersensitivity in mice, but puzzles still remain with respect to the underlying hyperactivation of corticotropin-releasing factor neurons. Herein, we employed maternal separation (MS) to establish mouse model of visceral hypersensitivity. The neuronal circuits associated with nociceptive hypersensitivity involved paraventricular nucleus CRF neurons by means of techniques such as behavioral test, pharmacology, molecular biology, retrograde neuronal circuit tracers, electrophysiology, chemogenetics and optogenetics. MS could predispose the elevated firing frequency of CRF neurons in PVN in murine adulthood, which could be annulled via the injection of exogenous GABA (0.3mM, 0.2µl) into PVN. The PVN-projecting GABAergic neurons were mainly distributed in the anterior ventral (AV) region in the bed nucleus of stria terminalis (BNST), wherein the excitability of these GABAergic neurons was reduced. Casp3 virus was utilized to induce apoptosis of GABA neurons in BNST-AV region, resulting in the activation of CRF neurons in PVN and visceral hyperalgesia. In parallel, chemogenetic and optogenetic approaches to activate GABAergic BNSTAV-PVN circuit in MS mice abated the spontaneous firing frequency of PVN CRF neurons and prevented the development of visceral hypersensitivity. A priori, PVNCRF-projecting GABAergic neurons in BNST-AV region participated in the occurrence of visceral hypersensitivity induced by MS. Our research may provide a new insight into the neural circuit mechanism of chronic visceral pain.